Biochemical markers for clinical monitoring of tissue perfusion - Janotka, Marek; Ostadal, Petr (Molecular and cellular biochemistry, 2021)
The assessment and monitoring of the tissue perfusion is extremely important in critical conditions involving circulatory shock. There is a wide range of established methods for the assessment of cardiac output as a surrogate of oxygen delivery to the peripheral tissues. However, the evaluation of whether particular oxygen delivery is sufficient to ensure cellular metabolic demands is more challenging. In recent years, specific biochemical parameters have been described to indicate the status between tissue oxygen demands and supply. In this review, the authors summarize the application of some of these biochemical markers, including mixed venous oxygen saturation (SvO2), lactate, central venous-arterial carbon dioxide difference (PCO2 gap), and PCO2 gap/central arterial-to-venous oxygen difference (Ca-vO2) for hemodynamic assessment of tissue perfusion. The thorough monitoring of the adequacy of tissue perfusion and oxygen supply in critical conditions is essential for the selection of the most appropriate therapeutic strategy and it is associated with improved clinical outcomes.
Keywords: Circulatory shock; mikrocirkulace; Hypoxia; biologické markery; monitorování fyziologických funkcí; Hemodynamic monitoring; Biomarkers; Monitoring, Physiologic; Spectroscopy, Near-Infrared; Lactate; Lactic Acid; kyselina mléčná; Hemodynamics; hemodynamika; Oxygen Consumption; blízká infračervená spektroskopie; lidé; Tissue perfusion; perfuze; Carbon Dioxide; prognóza; hypoxie; Arteries; Perfusion; Oxygen; glukosa; Oxygen saturation; Glucose; oxid uhličitý; Microcirculation; Prognosis; arterie; kyslík; spotřeba kyslíku; Humans